1999
DOI: 10.1073/pnas.96.14.8283
|View full text |Cite
|
Sign up to set email alerts
|

Stress-induced behaviors require the corticotropin-releasing hormone (CRH) receptor, but not CRH

Abstract: Corticotropin-releasing hormone (CRH) is a central regulator of the hormonal stress response, causing stimulation of corticotropin and glucocorticoid secretion. CRH is also widely believed to mediate stress-induced behaviors, implying a broader, integrative role for the hormone in the psychological stress response. Mice lacking the CRH gene exhibit normal stress-induced behavior that is specifically blocked by a CRH type 1 receptor antagonist. The other known mammalian ligand for CRH receptors is urocortin. No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
138
3
2

Year Published

2000
2000
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 225 publications
(152 citation statements)
references
References 53 publications
9
138
3
2
Order By: Relevance
“…Mice with deletions of the CRH gene exhibit normal stress-induced behavior, confirming that CRH may not be the only physiologically active ligand of CRH receptors. If CRH is absent, other neuropeptides such as urocortin or other yet-to-be identified molecules acting at CRH1 or CRH2 receptors (and possibly CRH receptors yet-to-be discovered) can serve as anxiogenic or depressogenic signals (Weninger et al 1999). Studies by Liebsch et al (1995Liebsch et al ( , 1999, Heinrichs et al (1997), and Skutella et al (1998), who used antisense probes directed against the mRNA-encoding CRH-R1 and CRH-R2 in rats, and also studies involving mouse mutants lacking CRH-R1, suggested that CRH-R1 mediates anxiety-like behavior (Timpl et al 1998;Smith et al 1998) (Figure 2).…”
Section: Knock-out or Transgenic Manipulation Of Crh And Corticosteromentioning
confidence: 99%
See 1 more Smart Citation
“…Mice with deletions of the CRH gene exhibit normal stress-induced behavior, confirming that CRH may not be the only physiologically active ligand of CRH receptors. If CRH is absent, other neuropeptides such as urocortin or other yet-to-be identified molecules acting at CRH1 or CRH2 receptors (and possibly CRH receptors yet-to-be discovered) can serve as anxiogenic or depressogenic signals (Weninger et al 1999). Studies by Liebsch et al (1995Liebsch et al ( , 1999, Heinrichs et al (1997), and Skutella et al (1998), who used antisense probes directed against the mRNA-encoding CRH-R1 and CRH-R2 in rats, and also studies involving mouse mutants lacking CRH-R1, suggested that CRH-R1 mediates anxiety-like behavior (Timpl et al 1998;Smith et al 1998) (Figure 2).…”
Section: Knock-out or Transgenic Manipulation Of Crh And Corticosteromentioning
confidence: 99%
“…The behavioral role of urocortin still needs to be clarified. This neuropeptide binds with higher affinity to both CRH receptors and this may explain why anxiety-like responses to stressors in CRH null mutant mice are indistinguishable from wildtype mice (Weninger et al 1999). In the absence of CRH, urocortin may bind to CRH-R1 compensating the loss of CRH.…”
Section: Knock-out or Transgenic Manipulation Of Crh And Corticosteromentioning
confidence: 99%
“…As mentioned above, LY354740 administration increased c-Fos expression in the EW (Figure 7i and 8), an oculomotor nucleus receiving projections from the pretectal nuclei. The EW has recently been implicated in the regulation of stress/anxiety via its urocortin-containing neurons (Vaughan et al, 1995;Kozicz et al, 1998;Weninger et al, 1999Weninger et al, , 2000Skelton et al, 2000;Kozicz, 2003), and was therefore grouped in the present study with the other stressrelated brain regions (Figure 7). …”
Section: C-fos Induction In Central Visual Regions By Systemic Ly354740mentioning
confidence: 99%
“…Besides oculomotor functions, recent reports suggest the involvement of the EW in stress responses, anxiolytic actions of chronic benzodiazepine administration, and alcohol consumption (Skelton et al, 2000;Weninger et al, 2000;Bachtell et al, 2003;Kozicz, 2003). The EW is the primary source of the novel corticotropin-related neuropeptide urocortin in the rat and mouse brain (Vaughan et al, 1995;Kozicz et al, 1998;Weninger et al, 1999). The functional role of urocortin pathway and activation of EW neurons is currently under intense investigation.…”
Section: Central C-fos After Anxiolytic Ly354740mentioning
confidence: 99%
“…Within the CNS and elsewhere, CRF acts primarily on CRFR1 [4,35,41], but can activate with less efficacy CRF receptor 2 (CRFR2) [22,39]. CRF related peptides, urocortin (Ucn) 1 and Ucn 3, can also elicit different aspects of fear and anxiety (behavioral manifestations of stress) by acting within specific brain regions [3,18,23].…”
Section: Introductionmentioning
confidence: 99%